2018
DOI: 10.1371/journal.pone.0195629
|View full text |Cite
|
Sign up to set email alerts
|

Overview and outcome of Hodgkin’s Lymphoma: Experience of a single developing country’s oncology centre

Abstract: Hodgkin’s Lymphoma (HL) reveals variable epidemiological and clinico-pathological features in different geographical locations. In this retrospective study, we aimed to assess the epidemiological and clinic-pathological features, and outcome of HL patients treated at one hemato-oncology centre in Erbil, northern Iraq. Medical records of 103 HL patients treated over more than six years were reviewed. Treatment outcome was evaluated by measuring the 5-year overall and progression-free survival rates. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
(34 reference statements)
0
11
1
4
Order By: Relevance
“…In this study, the individual's gender seems to be predominantly male for all histological types, therefore, there was no statistically signi cant difference for this variable, despite this, studies report that in some regions the NSHL affects young women in a greater proportion (10); (19).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In this study, the individual's gender seems to be predominantly male for all histological types, therefore, there was no statistically signi cant difference for this variable, despite this, studies report that in some regions the NSHL affects young women in a greater proportion (10); (19).…”
Section: Discussioncontrasting
confidence: 54%
“…The primary tumor location in this study was more common in cervical lymph nodes (65%) and mediastinum (10%) and there was no statistically signi cant difference between histological types. Corroborating this, research carried out at the Iraq Oncology Center found that HL affects cervical and mediastinal lymph nodes more frequently (10). Another study also shows that about two thirds of cases of HL have cervical lymphadenopathy HL rarely has extranodal involvement, which commonly affects extranodal organs, such as skin, bones and gastrointestinal tract (20).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The lack of an in-house radiotherapy service has led to underutilization of RT; the option of using a single modality i.e. chemotherapy has been described in previous studies [918]. The National Cancer Institute of Canada Clinical Trials Group (NCIC CTG) HD.6 trial compared 4–6 cycles of ABVD alone with subtotal nodal irradiation, adding ABVD only in patients displaying an unfavorable risk profile.…”
Section: Discussionmentioning
confidence: 99%
“…Staging procedures used, including data of history, clinical examination, contrast-enhanced computed tomography (CECT) or positron emission tomography (PET-CT), and bone marrow examination, were recorded. Bulky disease was defined as lymph node mass >10 cm in diameter or mediastinal mass exceeding one-third of the maximum chest cavity on an upright posteroanterior chest radiograph or CECT [9]. Patients with stage I, IIA, and IIB (non-bulky with no extranodal disease) were considered to have early-stage disease.…”
Section: Methodsmentioning
confidence: 99%